Pemimpin Pendidikan Islam Sebagai Interprenaurship - Muhamad Qomarudinul Huda; Susanto Susanto (Jurnal Kajian Pendidikan Islam, 2023)
A leader. The person's behavior and deeds are exemplary, in other words being role models. The prevalence of our society sees that understanding is the meaning and purpose of the uswatun hasanah words contained in the Qur'an. The meaning is to imitate the Prophet Muhammad (sallallahu 'alaihi wa sallam). We have understood that education is a series of efforts that guide, direct the human potential of life in the form of basic abilities and learning ability, so that there is a change in his personal life, as individual mujluq, and social and in relation to the natural environment in which he lives . The process is always in the Islamic values, the values ​​that gave birth to the norms of shari'ah and akhlak al-karimah.